A Supported Bismuth Halide Perovskite Photocatalyst for Selective Aliphatic and Aromatic C–H Bond Activation. (23rd January 2020) - Dai, Yitao; Poidevin, Corentin; Ochoa‐Hernández, Cristina; Auer, Alexander A.; Tüysüz, Harun
Abstract: Direct selective oxidation of hydrocarbons to oxygenates by O2 is challenging. Catalysts are limited by the low activity and narrow application scope, and the main focus is on active C−H bonds at benzylic positions. In this work, stable, lead‐free, Cs3 Bi2 Br9 halide perovskites are integrated within the pore channels of mesoporous SBA‐15 silica and demonstrate their photocatalytic potentials for C−H bond activation. The composite photocatalysts can effectively oxidize hydrocarbons (C5 to C16 including aromatic and aliphatic alkanes) with a conversion rate up to 32900 μmol gcat −1 h −1 and excellent selectivity (>99 %) towards aldehydes and ketones under visible‐light irradiation. Isotopic labeling, in situ spectroscopic studies, and DFT calculations reveal that well‐dispersed small perovskite nanoparticles (2–5 nm) possess enhanced electron–hole separation and a close contact with hydrocarbons that facilitates C(sp 3 )−H bond activation by photoinduced charges. Abstract : Besser mit Bismut : Eine Reihe von kleinen Bismuthalogenid‐Perowskit‐Nanopartikeln auf einem Träger aus mesoporösem Siliciumdioxid wurde hergestellt. Sie stellen vielversprechende Photokatalysatoren für selektive aromatische und aliphatische C‐H‐Bindungsaktivierung unter Bestrahlung mit sichtbarem Licht dar.